Intravascular forward-looking ultrasound transducers for microbubble-mediated sonothrombolysis - Jinwook Kim (Nature Portfolio, 2017)
Abstract Effective removal or dissolution of large blood clots remains a challenge in clinical treatment of acute thrombo-occlusive diseases. Here we report the development of an intravascular microbubble-mediated sonothrombolysis device for improving thrombolytic rate and thus minimizing the required dose of thrombolytic drugs. We hypothesize that a sub-megahertz, forward-looking ultrasound transducer with an integrated microbubble injection tube is more advantageous for efficient thrombolysis by enhancing cavitation-induced microstreaming than the conventional high-frequency, side-looking, catheter-mounted transducers. We developed custom miniaturized transducers and demonstrated that these transducers are able to generate sufficient pressure to induce cavitation of lipid-shelled microbubble contrast agents. Our technology demonstrates a thrombolysis rate of 0.7 ± 0.15 percent mass loss/min in vitro without any use of thrombolytic drugs.